Sosialisasi Pencegahan Stunting dan Pemberian Makanan Tambahan (PMT) di Desa Pangkalan Indarung - Ismandianto I; Anggra Fadilla; Alyssa Septiawita; Aidura Izzara; Ayuni Safika; Nova Riani; Rifka Bahagiati; Robert Frans Antonio Worabay; Ulva Nurfajria (Yayasan Daarul Huda Kruengmane, 2023)
Stunting is a global nutritional problem that often occurs in poor and developing countries. Stunting is associated with an increased risk of morbidity and mortality, as well as suboptimal brain development, including delays in the development of motor and intellectual skills. Stunting describes chronic malnutrition that begins in childhood, during growth and development. Delays in growth and development in children under 5 years can be caused by many things. This activity was carried out in Pangkalan Indarung Village, Singingi District, Kuantan Singingi Regency. Due to the village community's lack of knowledge about stunting, Riau University KKN students collaborated with the posyandu to re-involve residents in stunting prevention outreach activities. This activity includes collecting data on toddlers and distributing stunting posters door to door so that we can better understand the situation in society. Stunting prevention outreach activities include two materials, namely Stunting Prevention and Exclusive Breastfeeding. The expected goal of this activity is that the people of Pangkalan Indarung Village can care more about health, especially nutritional intake so that they can prevent stunting.